Paraguay’s Path Toward the Simplification of Procedures in the Approval of GE Crops - Benítez Candia, Nidia; Fernández Ríos, Danilo; Vicién, Carmen (Frontiers in Bioengineering and Biotechnology, 2020)
Agricultural biotechnology was first regulated in Paraguay in 1997. The first update to the country’s regulatory framework came in 2012, motivated by the need to keep up with current technologies. As part of this process, in late 2012, the Paraguayan Ministry of Agriculture (MAG) joined the Partnership for Biosafety Risk Assessment and Regulation, led by ILSI Research Foundation. The purpose of the program was the development of capacity building activities. As a result, the regulatory authorities in Paraguay incorporated the problem formulation approach to environmental risk assessment into their regulatory processes, leading to improved efficiency, with more timely decisions. Shifting to a problem formulation-based decision-making system was not straightforward, since practice and experience are always required to make professional risk assessors. Despite the continuity of approvals, there was a lag in the response time reflected in the number of events approved. During 2019, a simplified approval procedure for events that have been assessed by sound and experienced regulatory systems was introduced. Acceptance of third-country assessments can allow regulatory systems to make better use of their human, financial, and institutional resources, and stimulate inter-agency cooperation. In this work we aim to present the recent evolution of the regulatory system in Paraguay toward the establishment of a simplified procedure for GE crops that have been already assessed by sound and experienced regulatory systems, taking into account several scientific criteria. Concepts such as the familiarity, history of safe use, substantial equivalence, transportability, problem formulation, and the use of the consensus documents, developed by Organization for Economic Co-operation and Development (OECD), Food and Agriculture Organization of the United Nations (FAO), World Health Organization (WHO) and other institutions, favors the acceptance of decision documents issued by third countries. This requires the commitment of governments to support the stability of the institutions responsible for the regulatory implementation and also encourages countries to put work into the preparation and publication of decision documents, which are the basis for the commercialization of GE events.